Bullying: Students' Soul Shakes, Destroyed, and Lost Learning Motivation, How to Bring it All Back? - Fitriati; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of the research is to find out the actions, causes, and efforts to overcome bullying at SDN Sarimulya . Data collection techniques are observation, interviews, and document studies. The results of the study (1) forms of bullying are categorized into three types of bullying, namely physical, verbal and relational bullying, (2) the causes of bullying are negative influences from the home environment, students feel powerful and feared in class, students feel jealous of other students, and lack of empathy for students with special needs, (3) efforts: the teacher approaches students who are involved in bullying, puts up pictures or posters about prohibitions on acts of bullying, and provides counseling about the dangers of bullying and collaborates with homeroom teachers and parents of students to overcome acts of bullying that are happen.